Astronautics - Walter, Ulrich (Weinheim : Wiley-VCH, 2008)
As a crewmember of the D-2 shuttle mission and a full professor of astronautics at the Technical University in Munich, Ulrich Walter is an acknowledged expert in the field. He is also the author of a number of popular science books on space flight and research.
Includes bibliographical references (p. 473-474) and index.
Keywords: Astronautics